PENGEMBANGAN BAHAN AJAR BERBASIS REFUTATION TEXT PADA MATERI ASAM BASA SMK-SMTI PONTIANAK - Prayuda, Riandi; Sartika, Rody Putra; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to produce teaching material based on refutation text that was feasible to be used and to find out student’s responses to the product that developed. The form of the research was Research and Development (R & D) which was adopted from the development of Kemp’s model. The subjects of this research is teaching materials based refutation text that was tested on class X students with industrial chemistry programs and laboratory testing analysis programs, which include XE, XF, XG and XH Classes at SMK-SMTI Pontianak by taking 9 students in each class who had high, medium, and low ability on acid-base material. Data collection instrument that was used were feasibility questionnaires and student responses questionnaires. The result showed that chemistry teaching material was very valid for contents feasibility (91,42%), very valid for presentation feasibility (92%), valid for language feasibility (80%), and valid for graphic feasibility (78,94%). The result of student’s responses showed that the teaching material has very high interpretations with total score of 81,88%. Thus, teaching material based on refutation text can be used as support in the learning process at school.  Keywords:  Teaching Materials, Refutation Text, Feasibility, Student’s Response, Acid Base